The effect of surface trimming and surface treatment of acrylic artifical teeth on the bond strength between acrylic artificial teeth and acrylic base - Marasigan, Mary Chris Joanne T.
The fracture between acrylic denture base material and artificial teeth is a common clinical occurrence in dental prosthodontic practice. A lot of experiments have been conducted to improve the quality of bond between acrylic pontic and acrylic resin base. However, the bond between acrylic denture teeth and denture base materials remains unreliable, inconsistent and unpredictable. Objectives: The study aims to determine the effect of surface trimming and surface treatment of acrylic artificial teeth on the bond strength between acrylic artificial teeth and acrylic base. Methods: The study was a true experimental study using Randomized Complete Block Design. 60 mandibular molars were used in this study and were randomly assigned to each group. The control group was composed of untrimmed acrylic teeth. The treatment groups were composed of acrylic teeth trimmed at different degrees and underwent monomer etching. All samples were processed simultaneously. Bond strengths were determined using Universal testing machine. The data were analyzed using two-way ANOVA with post Hoc test using Tukey's HSD (a=0.05). Results: Samples that were untrimmed yielded the highest bond strength and was statistically significant (p<0.05) compared to those that were trimmed at 1mm and 3mm. In addition, samples that received monomer etching had higher bond strength and was statistically significant (p<0.05) compared to those that have not undergone surface treatment. Conclusions: There are significant differences between the bond strengths of artificial acrylic teeth that have undergone surface treatment (methyl metacrylate monomer etching) and acrylic denture base compared to those that have not undergone surface treatment. Also, there are significant differences between the bond strengths of untrimmed artificial acrylic teeth than acrylic artificial teeth that are trimmed at 1mm and 3mm.